Comparative efficacy of interferon β versus glatiramer acetate for relapsing-remitting multiple sclerosis. Issue 9 (30th December 2014) - La Mantia, Loredana; Di Pietrantonj, Carlo; Rovaris, Marco; Rigon, Giulio; Frau, Serena; Berardo, Francesco; Gandini, Anna; Longobardi, Anna; Weinstock-Guttman, Bianca; Vaona, Alberto
Abstract : Interferon β (INFβ) and glatiramer acetate (GA) are widely used in patients with relapsing–remitting multiple sclerosis (RRMS). However, it is still unclear whether they have different efficacy. We performed a systematic search of head-to-head trials for gaining objective reliable data to compare the two drugs, using the Cochrane Collaboration methodology. We identified five randomised-controlled trials (RCTs) (2858 participants) comparing directly INFβ versus GA in RRMS. All studies were at high risk for attrition bias. Both therapies showed similar efficacy at 24 months, considering clinical (patients with relapse or progression) and one MRI activity (enhancing lesions) measure. At 3 years, evidence from a single study showed that the relapse rate was higher in the INFβ group than in the GA group (risk ratio 1.40, 95% CI 1.13 to 1.74, p 0.002). However, the average reduction in T2-weighted and T1-weighted lesion volume was significantly greater in the INFβ group than in the GA group (mean difference (MD) −0.58, 95% CI −0.99 to −0.18, p 0.004, and MD −0.20, 95% CI −0.33 to −0.07, p 0.003, respectively). The number of participants who dropped out of the studies because of adverse events was similar in the two groups. These data support clinicians in the use of these therapies, based on their similar safety and efficacy in the prevention of disease activity, although the different effect on MRI measures and the different tolerability might have a role in the therapeutic choice at the individual level.